Translation of Idiomatic Expressions in Comedy Movies: A Case Study of "Bad Boys" - Abbas, Ahmed Mohamed Sgair et al. (University of Science and Technology, Sana'a, Faculty of Humanities and Social Sciences, Translation Program, 2025)
Idiomatic expressions present a significant challenge in translation due to their cultural and contextual specificity, often requiring strategies that go beyond literal translation. This research examines the translation of idiomatic expressions in movies, focusing on the Bad Boys film as a case study. It focuses on identifying the idiomatic expressions along with their translations and investigating the strategies employed by translators to overcome these difficulties. The researchers followed the analytic comparative method and used Baker's (1992) taxonomy of the strategies above the word level. The findings indicate that paraphrasing is the dominant strategy among the strategies employed which reflects the challenges inherent in translating idiomatic expressions, particularly in comedic contexts where humor is often reliant on cultural nuances. The study found a low frequency of strategies involving idioms with similar meanings and forms, indicating difficulty in finding direct equivalents that retain both meaning and structure which highlights the necessity for translators to prioritize meaning over form, often leading to creative adaptation. The study highlights the inherent challenges in maintaining humor during translation, especially when dealing with culturally specific references.
Keywords: Translation; Idiomatic; Expressions